Effect of welding current on the microstructure, residual stresses, mechanical properties and nano-mechanical behaviour of P-TIG welded TiNi binary shape-memory alloy. (September 2022) - Asif, Huzaifa; Imran Khan, M.; Shehbaz, Tauheed; Nawaz Khan, Fahd; Iltaf, Asim; Junaid, Massab
In the present work, an autogenous TIG welding technique was used to join 2 mm thick sheets of a TiNi binary shape-memory alloy at three different values of current (80 A, 90 A and 100 A). The effects of the welding current on microstructures, residual stresses, mechanical properties and nano-mechanical behaviour were investigated. Microstructure analysis revealed that with an increase in current, the columnar grain size decreased, which had a significant effect on mechanical properties. The tensile strength of the weldment at 100 A was ∼92% of that base alloy's (BA) and elongation of approx. 14%. The reduction in elongation was due to the formation of Ti2 Ni and Ti3 Ni4 type precipitates. The microhardness profile in all the weldments showed an increase of approx. 30% between the base alloy and the fusion zone due to the formation of Ti2 Ni and Ti3 Ni4 type precipitates during welding. Residual stress analysis suggested the tensile residual stresses in the longitudinal direction are minimum in the weldment performed at 100 A. The nanoindentation results revealed that the weldment obtained at 100 A had the least plastic deformation (∼45.5% less than the 80 A weldment) owing to a decrease in inter-dendritic spacing and high proportion of IMCs: Ti2 Ni and metastable Ni4 Ti3 .